Teachers’ Pedagogical Competence, Classroom Management Skills, and Students’ Academic Achievement Among Selected Public City Schools Division in the Province of Laguna - Dumaguing, Marife L.; Yango, Antonio R. (Technium Social Sciences Journal, 2023)
Education is essential for nation-building and teachers are change advocates who support students’ aspirations. Pedagogical competence and high-quality teachers are essential for future growth and economic vitality. Classroom management is essential for students’ academic achievement and behavioral problems. This study aimed to determine teachers’ level of pedagogical competence, classroom management skills, and the relationship between teachers’ level of pedagogical competence, classroom management skills, and students’ academic achievement, and how predictive they are in public city school divisions, Laguna. The study found that the average weighted mean of 3.25 revealed that teachers’ level of pedagogical competence was very high. The teachers’ level of classroom management skills obtained a weighted mean of 3.30, which revealed that the respondents had very good classroom management skills. Out of the 1000 total population, 278 teachers were selected among the public city schools division. The student’s academic grades ranged from 85-89 with the highest frequency of 173 with a percentage of 62.23. The relationship between teachers’ level of pedagogical competence and level of classroom management skills revealed that there is no significance in the probability acquired greater than the significance level of 0.05. However, the relationship between the teachers’ level of pedagogical competence and students’ academic achievement based on their GPA got a p-value for “Diversity of Learners” obtained at 0.049, which revealed that there is a “significant relationship.” The relationship between the teachers’ level of classroom management skills and students’ academic achievement received a p-value of 0.418, which revealed that there is no significant relationship. The results implied that the teachers’ level of classroom management skills has nothing to do with students’ academic achievement and may be due to the diversity of learners.